Influence of Stable Data Location on Wind Energy Prediction - Živković, Predrag; Tomić, Mladen; Mojsovski, Filip; Barz, Cristian; Dimitrijević Jovanović, Dragana; Cajić, Petar (University of Niš, Faculty of Mechanical Engineering in Niš, 2019)
Obtaining of all acceptable locations is one of the main tasks for siting of wind turbines. The economical factors are usually very limiting. Very thorough analyses are needed in order to ensure the finalization of the project. Nevertheless, even after all the steps are done, some problems may occur. One of them is the real status of the winds in the investigated area. This paper focuses on the influences of the chosen main meteorogical station, if there are more than one available in the mezzo model of interest. The estimations were obtained using the WAsP simulation software. The results are compared by means of the quality and quantity of the wind data and capacity factor. This paper is concerned by the National Program of Energy Efficiency, project number: TR33036, funded by the Government of Republic of Serbia.
Keywords: wind power assessment; complex terrain; CFD; WAsP; climatic changes